A “Sürek” in Alevism: Sufis and Music in Alevism in Adıyaman - Özdemir, Erhan (Journal of Alevism-Bektashism Studies, 2023)
In this study, the collective cultural structure of the Alevi belief structure, which appears under the name of Sofilik in Adıyaman province of Turkey, will be analyzed through the relationship between ritual and music. This community, which has an Alevi-Kurdish identity, differs from other Alevi groups living in Turkey with its unique cultural, belief and musical structure. It is not possible to talk about complete homogeneity among Alevis in terms of belief and non-belief rituals. This is due to factors such as ethnicity, language, ocak and geography. Music and semah/dem, one of the most important cultural elements of Alevism, exhibit a unique structure among the Sofis. This unique structure, like the Sofis within the Alevi belief, ensures the continuity of the tradition by carrying collective and cultural memory. There are no written sources on the tradition of sofism in Adıyaman province. For this reason, the study we have conducted has the characteristic of being a first in this field, as well as being difficult due to the lack of scientific resources on the group we have identified and the fact that they continue their belief structure as a closed community. The geographical limitation of the study is the provinces of Adıyaman and Istanbul. The data obtained through face-to-face interviews with the people reached are subjected to evaluation in the relevant parts of the study. The study includes the analysis and evaluation of the historical and belief narratives obtained as a result of the field research, as well as the analysis and evaluation of the determinations about the music and semah/demand in the ritual they call möhbet/muhabbet. In addition, the creation of the universe, the place of women in the faith, the sanctity of Hz. Ali, Hz. Hussein’s position in the hierarchy of beliefs, the Karbala incident and the position of Hz. Hussein in the hierarchy of beliefs, their perspective on the twelve ministries and the cults of visitation were tried to be conveyed in line with the data obtained from field research. Music, which has an important place in the Sofism tradition, is presented with its social and contextual dimension rather than its technical dimension.
Keywords: Alevi; Music; Sofi; Adıyaman; Semah